Automatic modulation recognition algorithm for MQAM signal - Huadi ZHANG; Huaxun LOU (Tongxin xuebao)
An automatic modulation recognition algorithm for MQAM signal was proposed.Firstly,the feature parameter F based on the fourth order cumulants was constructed to classify the square QAM and the cross QAM.Secondly,the compactness of zero center normalized instantaneous amplitude was calculated to identify the 16QAM from the square QAM.Thirdly,the baud rate was estimated by frequency spectrum of amplitude square,and timing was synchronized to delete the ISI and resume the relatively ideal constellations.And aiming at the 32QAM and the 128QAM,two different clustering radii were set,and clustering point density was got respectively by the subtractive clustering algorithm,and then the 32QAM and the 128QAM was classified depending on the difference of density value.In the same way,the 64QAM and the 256QAM were classified.The proposed algorithm can recognize five kinds of QAM signals，including 16QAM signals,32QAM signals,64QAM signals,128QAM signal and 256QAM signal without prior knowledge of frequency and baud rate.Furthermore,the proposed algorithm does not need complex iterative process,which can be applied in practical signal recognition.